2009
DOI: 10.1111/j.1872-034x.2009.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EphA2, MMP‐9, and MVD‐CD34 in hepatocellular carcinoma: Implications for tumor progression and prognosis

Abstract: Overexpressions of EphA2 and MMP-9 relate to tumor progression, metastasis, and prognosis in HCC. The present study suggests that EphA2 is associated with key mediators of angiogenesis and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 25 publications
(49 reference statements)
6
42
1
Order By: Relevance
“…MMP9 is an important member of MMP family which is pivotal in degrading the basement membrane and has been proven to facilitate tumor invasion and metastasis in many types of cancer cells (19,28,29). It has also been shown that the invasive and metastatic capabilities of HCC were restrained by suppression of MMP9 (30,31). Indeed, in this study, we found that inhibition of MMP9 expression was associated with the suppression of HCC cell migration and invasion in vitro after overexpression of RIG-I.…”
Section: Discussionsupporting
confidence: 55%
“…MMP9 is an important member of MMP family which is pivotal in degrading the basement membrane and has been proven to facilitate tumor invasion and metastasis in many types of cancer cells (19,28,29). It has also been shown that the invasive and metastatic capabilities of HCC were restrained by suppression of MMP9 (30,31). Indeed, in this study, we found that inhibition of MMP9 expression was associated with the suppression of HCC cell migration and invasion in vitro after overexpression of RIG-I.…”
Section: Discussionsupporting
confidence: 55%
“…Sixteen Eph receptors, including EphA-1-A-10 and B-1-B-6, play an important role by specifically binding to the corresponding ligand in the growth and development of some diseases. 31 Studies have shown that EphA-2 is highly expressed in many cancers, including lung cancer, 32 hepatocellular carcinoma, 33 and breast cancer, 34 and have found that EphA-2 promoted tumor angiogenesis, cell proliferation, invasion and metastasis, and can predict the survival time and recurrence in patients with malignant tumors, also serving as a marker for studying the effects of new drugs. Here, we reported expression of EphA-2 in thyroid cancer for the first time.…”
Section: Discussionmentioning
confidence: 98%
“…33,34 CD-34 immunolabeling has also been recently associated with invasion and metastasis. 35 However, in contradiction with the previously mentioned studies, in a small series published by Zeng et al 36 including 70 consecutive patients treated with resection or transplantation, the authors reported that lower microvascular count confers a higher risk of recurrence after resection. Such inconsistency highlights the importance of adequate statistical power as a prerequisite to any study attempting to qualify or validate new prognostic markers in HCC.…”
Section: Microvessel Densitymentioning
confidence: 88%